CP-6 Modification of natural products by the Chan-Lam reaction: Chemical space expansion and antibacterial activity - Pérez Hernández, Edwin G.; Hormazábal, Cristóbal; Sanchez Velasco, Oriel Alfredo (Revista Productos Naturales, 2025)
Natural products play a crucial role in drug discovery and development, as evidenced by the fact that approximately 75% of antibacterial compounds introduced clinically in the last 40 years are derived from natural sources, including microbes, plants, and animals
Keywords: Boldine; viridicatin; isovanillin; Chan-Lam coupling; Copper-catalyzed